CHANGES IN THE NUMBER OF MICROORGANISMS IN LIGHT GRAY SOILS CONTAMINATED WITH INDUSTRIAL WASTE - Khalikova Surayyo Narzullayevna (Web of Journals Publishing, 2025)
This article presents the results of studying changes in the number of certain soil microorganisms under the influence of industrial waste contamination of light gray soils distributed in the Guzar district of Kashkadarya region.
Keywords: Actinomycetes, micromycetes, oligonitrophils, ammonifiers, humus, carbon monoxide, nitrogen dioxide, nitrogen oxide, hydrocarbons, sulfur dioxide.